Nonlinear increase in seawater ⁸⁷Sr ∕ ⁸⁶Sr in the Oligocene to early Miocene and implications for climate-sensitive weathering - Stoll, Heather; id_orcid:0 000-0002-2953-7835; Pena, Leopoldo D.; Hernández-Almeida, Iván; id_orcid:0 000-0002-9329-8357; Guitián, José; Tanner, Thomas; Pälike, Heiko (Copernicus, 2024)
The ⁸⁷Sr / ⁸⁶Sr of marine carbonates provides a key constraint on the balance of continental weathering and hydrothermal Sr fluxes to the ocean, and the mid-Oligocene to mid-Miocene period features the most rapid rates of increase in the ⁸⁷Sr / ⁸⁶Sr of the Cenozoic. Because previous records of the ⁸⁷Sr / ⁸⁶Sr increase with time were based on biostratigraphically defined age models in diverse locations, it was difficult to unambiguously distinguish million-year-scale variations in the rate of ⁸⁷Sr / ⁸⁶Sr change from variations in sedimentation rate. In this study, we produce the first ⁸⁷Sr / ⁸⁶Sr results from an Oligocene to early Miocene site with a precise age-model-derived orbital tuning of high-resolution benthic δ¹⁸O at Equatorial Pacific Ocean Drilling Program (ODP) Site 1218. Our new dataset resolves transient decreases in ⁸⁷Sr / ⁸⁶Sr, as well as periods of relative stasis. These changes can be directly compared with the high-resolution benthic δ¹⁸O at the same site. We find that slowing of the rate of ⁸⁷Sr / ⁸⁶Sr increase coincides with the onset of Antarctic ice expansion at the beginning of the mid-Oligocene glacial interval, and a rapid steeping in the ⁸⁷Sr / ⁸⁶Sr increase coincides with the benthic δ¹⁸O evidence for rapid ice retreat. This pattern may reflect either northward shifts in the Intertropical Convergence Zone precipitation to areas of nonradiogenic bedrock and/or lowered weathering fluxes from highly radiogenic glacial flours on Antarctica. We additionally generate the first ⁸⁷Sr / ⁸⁶Sr data from ODP Site 1168 on the Tasman Rise and Integrated Ocean Drilling Program (IODP) Site 1406 of the Newfoundland Margin during the Oligocene to early Miocene to improve the precision of age correlation of these Northern Hemisphere and Southern Hemisphere midlatitude sites and to better estimate the duration of early Miocene hiatus and condensed sedimentation. ISSN:1814-9324 ISSN:1814-9332